Wessex Tales - Hardy, Thomas (Wordsworth Editions Ltd, 1995)
Wessex Tales includes the stories An Imaginative Woman, The Three Strangers, The Withered Arm, Fellow-Townsmen, Interlopers at the Knap, and The Distracted Preacher. Based on fact, the narratives describe the life, culture, and ways of the inhabitants of Wessex.
Keywords: Classics (Hardy)-Short stories-Fiction